Correction to: Whole tumor analysis reveals early origin of the TERT promoter mutation and intercellular heterogeneity in TERT expression - Appin, Christina; Hong, Chibo; Suwala, Abigail Kora; Hilz, Stephanie; Mathur, Radhika; Solomon, David A; Smirnov, Ivan V; Stevers, Nicholas O; Shai, Anny; Wang, Albert; Berger, Mitchel S; Chang, Susan M; et al. (Neuro-Oncology, 2024)
The TERT promoter mutation (TPM) is acquired in most IDH-wildtype glioblastomas (GBM) and IDH-mutant oligodendrogliomas (OD) enabling tumor cell immortality. Previous studies on TPM clonality show conflicting results. This study was performed to determine whether TPM is clonal on a tumor-wide scale.We investigated TPM clonality in relation to presumed early events in 19 IDH-wildtype GBM and 10 IDH-mutant OD using 3-dimensional comprehensive tumor sampling. We performed Sanger sequencing on 264 tumor samples and deep amplicon sequencing on 187 tumor samples. We obtained tumor purity and copy number estimates from whole exome sequencing. TERT expression was assessed by RNA-seq and RNAscope.We detected TPM in 100% of tumor samples with quantifiable tumor purity (219 samples). Variant allele frequencies (VAF) of TPM correlate positively with chromosome 10 loss in GBM (R = 0.85), IDH1 mutation in OD (R = 0.87), and with tumor purity (R = 0.91 for GBM; R = 0.90 for OD). In comparison, oncogene amplification was tumor-wide for MDM4- and most EGFR-amplified cases but heterogeneous for MYCN and PDGFRA, and strikingly high in low-purity samples. TPM VAF was moderately correlated with TERT expression (R = 0.52 for GBM; R = 0.65 for OD). TERT expression was detected in a subset of cells, solely in TPM-positive samples, including samples equivocal for tumor.On a tumor-wide scale, TPM is among the earliest events in glioma evolution. Intercellular heterogeneity of TERT expression, however, suggests dynamic regulation during tumor growth. TERT expression may be a tumor cell-specific biomarker.